Unsettling nature : ecology, phenomenology, and the settler colonial imagination - Eggan, Taylor, 1986- (Under the sign of nature., 2022)
"Drawing broadly on environmental philosophy, literary theory, settler colonial studies, decolonial theory, and speculative realism, Eggan quarries uncanny depictions of the natural world to unsettle not just the concept of nature but the coloniality of Nature. Unsettling Nature at once critiques Heidegger's home(l)y phenomenology and brings it forward through chapters on Willa Cather, D. H. Lawrence, Olive Schreiner, and Doris Lessing. The book concludes with a speculative proposal to transform eco-phenomenology into "exo-phenomenology," which emphasizes ways of being and perceiving that bring us out of ourselves into contact with the Other, and into an encounter with the self as Othered"--